Designing with biobased composites: understanding digital material perception through semiotic attributes. (15th March 2023) - Thundathil, Manu; Nazmi, Ali Reza; Shahri, Bahareh; Emerson, Nick; Müssig, Jörg; Huber, Tim
Abstract: Biobased composites, which are considered a sustainable alternative to plastics, are yet to create a significant influence on product design and manufacturing. A key reason for this is perceptual handicaps associated with biobased composites and this study was aimed at understanding the mechanisms behind biocomposite perception, in the context of digital visuals. This study of digital biocomposite visuals demonstrated that material perception is influenced by the visual characteristics of the material. Data analysis of the perceptual attributes of the materials pointed towards clear 'clustering' of the materials against these attributes. Analysis shows that visual features like fibres and surface appearance may impact aesthetic and functional evaluation and there is no effect on age, gender or polymer type. We also propose a reference framework to categorise biobased composites based on visual order.